Density functional study of porphyrin distortion effects on redox potential of heme. Issue 3 (2nd September 2017) - Imada, Yasuhiro; Nakamura, Haruki; Takano, Yu
Abstract : Heme is involved in various biochemical roles in hemoproteins. In the present study, the effect of heme distortion on the redox potential was systematically investigated with density functional calculations. We focused on the ruffled and saddled distortions of heme, which correspond to the two lowest‐frequency normal modes. Our computations demonstrated that the ruffled distortion tended to reduce the redox potential of heme and that the transition of the electronic configuration occurred from (dxz, dyz ) 3 (dxy ) 2 to (dxz, dyz ) 4 (dxy ) 1 . In contrast, the saddled distortion had a tendency toward an increase in the redox potential, and no transition of the electronic configuration occurred. In experiments, these tendencies were found in the relationship between with the heme distortions and the redox potentials in cytochrome c 3 . © 2017 Wiley Periodicals, Inc. Abstract : The relationship between heme distortions in ruffling and saddling modes and the redox potentials has systematically been investigated using density functional theory. The ruffled deformation basically decreased the redox potential and changed the electronic configuration. In contrast, the saddled deformation monotonically increased the redox potential, while maintaining the electronic configuration. Our computations qualitatively agreed with the experimental data of hemoproteins and synthetic Fe‐porphyrin complexes.